The outcome to axitinib or everolimus after sunitinib in metastatic renal cell carcinoma. Issue 7 (August 2018) - Iacovelli, Roberto; Cossu Rocca, Maria; Galli, Luca; Sabbatini, Roberto; De Giorgi, Ugo; Santini, Daniele; Facchini, Gaetano; Mosca, Alessandra; Atzori, Francesco; Zucali, Paolo; Fornarini, Giuseppe; Massari, Francesco; et al.
Abstract : We aimed to investigate the different outcomes in patients with metastatic renal cell carcinoma treated with second-line axitinib or everolimus after sunitinib. Patients treated in 16 oncological centres in Italy were included, and those receiving axitinib or everolimus from January 2013 onwards were analysed for outcomes. Descriptive statistical tests were used to highlight differences between groups. The Kaplan–Meier method was used to estimate overall survival (OS) and progression-free survival (PFS). Data on 634 patients with metastatic renal cell carcinoma treated with first-line sunitinib have been obtained. A total of 182 patients received a second-line therapy with everolimus (79 patients, 43%) or axitinib (103 patients, 57%), respectively. The median PFS was 4.6 [95% confidence (CI): 2.6–6.5] months for patients treated with everolimus and 5.5 (95% CI: 4.3–6.7) months for patients treated with axitinib ( P =0.7). The median OS was 13.9 (95% CI: 10.4–17.4) months for patients treated with everolimus and 12.0 (95% CI: 7.9–16.2) months for patients treated with axitinib ( P =0.3). No differences were found based on length of first-line treatment. Major limitations are the retrospective nature of the study and the lack of a prospective evaluation of the progression. This study reports no significantly differences between everolimus and axitinib in terms of both PFS and OS. Furthermore, the length of first-line treatment cannot be used as such a predictive factor and cannot suggest the use of a molecule compared with another.